The interactive effect of empathy and motor cortex stimulation on hand gesture comprehension. (April 2020) - Jospe, Karine; Flöel, Agnes; Lavidor, Michal
Abstract: Previous research has demonstrated that the Action-Observation Network (AON) is involved in both emotional-embodiment (empathy) and action-embodiment mechanisms. In the current study, we hypothesized that interfering with the AON will impair action recognition and that this impairment will be modulated by empathy levels. Fifty-two participants conducted a semantic decision task of hand gesture recognition, while we interfered with the AON by applying active (n = 26) or sham (n = 26) transcranial Direct Current Stimulation (tDCS) to the hand area of the primary motor cortex. We found that interfering with the AON impaired the performance of participants with high empathy levels and enhanced the performance of participants with low empathy. This finding suggests that the embodiment module may be flexible, and that it can be enhanced in individuals with low empathy by simple manipulation of motor activation. Highlights: Action recognition modulated by empathy levels. Cortical stimulation effect differs between individuals with high or low empathy. Individual differences found in the use of grounded cognition. Embodiment module may be flexible and can be enhanced. Motor stimulation can impair or enhance performance depending on their empathy.